REVITALISASI SEKTOR AGROINDUSTRI UNTUK MENINGKATKAN KETAHANAN PANGAN DAN PENGENTASAN PENGANGGURAN DAN KEMISKINAN DI PROPINSI JAWA TIMUR - Musdholifah, ; Ady Soejoto, (Pendidikan Ekonomi, 2011)
The study is aimed to scrutinize the role of agro-industrial sector in boosting the people income, employment, to analyze backward and forward effect relation of agro-industrial sector and the output of farming sector, and to analyze the variables influencing the production increase of agro-industrial sector, and determine the prioritized farming commodities to create higher employment in East Java Province.  The data were analyzed with input-output and econometric analyses. Econometric analysis reveals that investment, export, and import have a positive association with the increased production of agro-industrial sector. In addition, theinput-output analysis shows that mills are a seeded sector if viewed from the distribution indicator, and food industries are a seeded sector if seen from the number of related sectors and sensitivity degree.